2018
DOI: 10.1016/j.celrep.2018.02.099
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Molecular Mechanisms Rescue mtDNA Disease in C. elegans

Abstract: SUMMARYGenetic instability of the mitochondrial genome (mtDNA) plays an important role in human aging and disease. Thus far, it has proven difficult to develop successful treatment strategies for diseases that are caused by mtDNA instability. To address this issue, we developed a model of mtDNA disease in the nematode C. elegans, an animal model that can rapidly be screened for genes and biological pathways that reduce mitochondrial pathology. These worms recapitulate all the major hallmarks of mtDNA disease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…However, the mutational heterogeneity that arises in this model, which includes point mutations as well as small indels, large deletions, and mtDNA depletion, has led to considerable debate about the pathogenic entity and whether point mutations are actually driving ageing 1114 . Recently described fly and worm POLG mtDNA mutators, which offer an attractive system for their powerful genetic approaches, also show evidence of this mutational heterogeneity 15,16,33 . However, while the first fly model equivalent to the POLG- mutator was homozygous lethal 15 , a similar model recently reported is not lethal 16 , raising uncertainty about the cause of the lethality.…”
Section: Discussionmentioning
confidence: 96%
“…However, the mutational heterogeneity that arises in this model, which includes point mutations as well as small indels, large deletions, and mtDNA depletion, has led to considerable debate about the pathogenic entity and whether point mutations are actually driving ageing 1114 . Recently described fly and worm POLG mtDNA mutators, which offer an attractive system for their powerful genetic approaches, also show evidence of this mutational heterogeneity 15,16,33 . However, while the first fly model equivalent to the POLG- mutator was homozygous lethal 15 , a similar model recently reported is not lethal 16 , raising uncertainty about the cause of the lethality.…”
Section: Discussionmentioning
confidence: 96%
“…Work in the nematode C . elegans has also shown that autophagy is required for the elimination of radiation-induced mtDNA damage [49], and that inactivation of the mitophagy-promoting factor Parkin results in increased abundance of point mutations in a mitochondrial mutator background and increased abundance of a deleterious mtDNA deletion when the mitochondrial unfolded protein stress pathway is activated [5052]. Overexpression of autophagy-promoting factors in Drosophila also reduced the frequency of a heteroplasmic deletion created by expression of a mitochondrially-targeted restriction endonuclease [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing the activity of PINK1 and Parkin in an otherwise WT C . elegans genetic background did not significantly influence the frequency of point mutations or a large mtDNA deletion, suggesting that this pathway does not ordinarily select against deleterious mtDNA mutations [5052]. Moreover, mutator mice do not exhibit an altered NS/S mutation ratio relative to WT mice [20, 26, 55], and mutator mice lacking the mitophagy-promoting factor Parkin do not exhibit an increased mtDNA mutation frequency or an altered NS/S mutation ratio relative to mutator mice [26].…”
Section: Discussionmentioning
confidence: 99%
“…Normal chow‐fed postabsorptive mice showed increased muscle mtDNA copy number at ages 6 and 12 months which is suggestive of increased mtDNA replication or reduced mitophagic flux, or both. These data are in contrast to the mtDNA depletion phenotype of the PolG mut/mut mouse and polg‐1(srh1) C. elegans in which copy number was reduced > 50% (Haroon et al., 2018; Trifunovic et al, 2004; Vermulst et al., 2008). Moreover, in contrast to PolG mut/mut , PolG +/mut mice showed no change in mtDNA replication capacity (He, Shumate, White, Molineux, & Yin, 2013); therefore, increased mitochondrial DNA replication is a possible mechanism of compensation to elevate the abundance of healthy DNA in muscle of PolG +/mut mice.…”
Section: Discussionmentioning
confidence: 77%